2004
DOI: 10.1002/pmic.200300843
|View full text |Cite
|
Sign up to set email alerts
|

A simple and inexpensive approach to interfacing high‐performance liquid chromatography and matrix‐assisted laser desorption/ionization‐time of flight‐mass spectrometry

Abstract: The ability to obtain the accurate mass of a protein in a complex sample mixture aids in determining its correct in vivo form. This is important when identifying post-translationally modified proteins, protein variants or isoforms. The central technique used to separate proteins, 2-dimensional gel electrophoresis offers excellent separation capabilities but does not provide adequate mass accuracy. In this study, an alternative method, liquid chromatography (LC) coupled with matrix-assisted laser desorption/ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The analysis of intact proteins is an important component of proteomic research as it yields information about post-translational modifications of proteins and the ability to detect other post-translational events leading to multiple products derived from a single gene 31 . Application of DESI-MS as an analysis tool for protein molecules in the field of proteomics is ideal due to its simplicity, speed of analysis for high throughput applications, and analytical specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of intact proteins is an important component of proteomic research as it yields information about post-translational modifications of proteins and the ability to detect other post-translational events leading to multiple products derived from a single gene 31 . Application of DESI-MS as an analysis tool for protein molecules in the field of proteomics is ideal due to its simplicity, speed of analysis for high throughput applications, and analytical specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of tandem mass spectrometry can often provide confident identifications, there is increasing interest in higher throughput approaches that exploit highly accurate mass measurements [3][4][5][6][7][8]. Earlier studies have shown [9,10] that utilizing accurate mass spectrometric measurements for MS based identification of peptides within Ϯ0.1 ppm uncertainty (tolerance) can allow significant levels of confidence in protein identifications, even from mixtures with the complexity of some smaller eukaryotic systems (e.g., yeast).…”
mentioning
confidence: 99%
“…The target deposition rate was 0.25 ml min Ϫ1 . A similar set up that has been developed and used previously for MALDI film deposition has been described elsewhere [9].…”
Section: Methodsmentioning
confidence: 99%